Stereoscopic vs. monoscopic photographs on optic disc evaluation and glaucoma diagnosis among general ophthalmologists: A cloud-based real-world multicenter study - Yang, Jingyuan; Qu, Yi; Zhao, Jianchun; Cong, Jingwu; Sun, Zixi; Du, Yunfeng; Yang, Gang; Ding, Dayong; Chen, Youxin; Cheng, Gangwei (Frontiers in Medicine, 2022)
Purpose: To investigate whether stereoscopic versus monoscopic viewing condition influences evaluation of optic disc photographs for morphologic features and glaucoma likelihood in a general ophthalmologist population from multicenters on a cloud-based platform. Methods: A cross-sectional study. 519 pairs of stereoscopic and monoscopic photographs of optic disc with adequate quality were selected and presented using an cloud-based platform. Twenty-one general ophthalmologists from 14 centers assessed 15 morphologic features based on 5R rules and estimated glaucoma likelihood for each assigned photograph. Main outcome measures were the agreement between estimates and ground truth and the inter-grader agreements. Results: There were good agreements between ground truth and both monoscopic and stereoscopic estimates (stereo κ 0.532 and mono κ 0.494). There was also substantial intra-grader agreement between monoscopic and stereoscopic evaluation of glaucoma likelihood (κ 0.636). In eyes with probable glaucoma, the accuracy of stereo method was greater than that of mono method (stereo 0.238 vs mono 0.118) When compared with ground truth, stereoscopic photographs had better agreement for disc size (stereo κ 0.447 vs mono κ 0.183), disc color (stereo κ 0.612 vs mono κ 0.549), neuroretinal rim shape (stereo κ 0.356 vs mono κ 0.274) on the whole. Stereoscopic method also had better inter-grade agreement for disc size, disc color, neuroretinal rim shape, and glaucoma likelihood (stereo κ 0.402vs mono κ 0.359) on the whole. Conclusions: In the evaluation of optic disc photographs for morphologic features and glaucoma likelihood, stereoscopic method showed superiority compared to monoscopic method for general ophthalmologists. Stereoscopic method is more likely to identify glaucomatous eyes which need medical intervention.